The regulation of AβPP expression by RNA-binding proteins - Westmark, Cara J.; Malter, James S. (Ageing research reviews, 2012)
► Multiple RBPs interact with distinct cis-elements in APP mRNA. ► hnRNP C and nucleolin bind to 3′-UTR cis-elements and mediate message stability. ► IRP1 binds to an IRE in the 5′-UTR of APP mRNA to regulate translation. ► FMRP and hnRNP C compete for binding to a CR G-rich element to modulate translation. ► APP mRNA is subject to diverse post-transcriptional regulatory processes. Amyloid β-protein precursor (AβPP) is cleaved by β- and γ-secretases to liberate amyloid beta (Aβ), the predominant protein found in the senile plaques associated with Alzheimer's disease (AD) and Down syndrome (Masters et al., 1985). Intense investigation by the scientific community has centered on understanding the molecular pathways that underlie the production and accumulation of Aβ Therapeutics that reduce the levels of this tenacious, plaque-promoting peptide may reduce the ongoing neural dysfunction and neuronal degeneration that occurs so profoundly in AD. AβPP and Aβ production are highly complex and involve still to be elucidated combinations of transcriptional, post-transcriptional, translational and post-translational events that mediate the production, processing and clearance of these proteins. Research in our laboratory for the past two decades has focused on the role of RNA binding proteins (RBPs) in mediating the post-transcriptional as well as translational regulation of APP messenger RNA (mRNA). This review article summarizes our findings, as well as those from other laboratories, describing the identification of regulatory RBPs, where and under what conditions they interact with APP mRNA and how those interactions control AβPP and Aβ synthesis.